A Marginal Effects Approach to Interpreting Main Effects and Moderation. (January 2022) - Busenbark, John R.; Graffin, Scott D.; Campbell, Robert J.; Lee, Eric Young
This Short Methodological Report builds on research about moderation practices by focusing on a marginal effects approach to interpreting how a main effect is informed by the presence of a moderating variable. Following a content analysis of published studies and a survey of management researchers, our findings suggest there is a great deal of confusion about the ways in which to interpret how a main effect may fluctuate owing to a moderating variable. We therefore provide explicit instructions on how to implement and interpret a marginal effects approach that depicts the nature of a main effect in the presence of a moderator. We use different scenarios and examples to illustrate how researchers can employ the marginal effects technique, which provides an indication of the relationship between the independent and dependent variables over different values of the moderator. We argue and demonstrate that the marginal effects approach helps resolve conflicting findings that may arise from using other prevailing techniques to interpret both main effects and moderation.